Evaluation of an intensified prevention program for 4th graders with increased caries risk using ICDAS. Issue 4 (16th September 2015) - Winter, Julia; Weber, Kristina; Martin, Katharina; Heinzel‐Gutenbrunner, Monika; Pieper, Klaus
Abstract : Background: In order to investigate correlations between specific parameters and dental caries, it is useful to record incipient and dentine lesions. Aim: The aim of this study was to evaluate the effect of a selective intensified preventive program (SIP) on oral health of fourth graders using ICDAS. Design: A cohort study was performed. ICDAS and DMFT index were recorded. Prevention and social factors were collected with psychometric questionnaires. The test group and the control group were parallelized using sociodemographic variables. Results: The participants in the fluoride varnish program in the test region showed a significantly lower caries experience than pupils in the control region. The bivariate analysis revealed that a migrant background had a negative impact on oral health whereas fissure sealants, use of fluoridated table salt, use of fluoride tablets, early start of toothbrushing and high social status exerted a positive influence on dental health. Stepwise backward logistic regression analysis confirmed that fissure sealants, a high social status and an early start of toothbrushing had a significant positive impact on dental health. Conclusion: The results of our study suggest that a SIP impedes the primary occurrence of incipient lesions and the transition from incipient to advanced lesions.